Research on the Impact of Meteorological Disaster Shocks and Risk Perception on Farmers’ Cooperative Pest and Disease Control Behavior - Zhiwu He; Xiuling Ding; Qian Lu (Agriculture)
Climate change, primarily characterized by rising global temperatures, has led to a continuous expansion in the area affected by pests and diseases. This poses a significant threat to national agricultural production and directly jeopardizes food security. Cooperative pest and disease control behavior represents a novel approach to pest and disease management and is an important measure for mitigating agricultural production risks. This study employs Probit and IVProbit models to empirically examine the impact of meteorological disaster shocks on cooperative pest and disease control behavior. The results show that both meteorological disaster shocks and their frequency significantly and positively influence cooperative pest and disease control behavior. Moreover, the perception of risk losses plays a mediating role in this relationship. The impact of meteorological disaster shocks on farmers’ cooperative pest and disease control behavior is heterogeneous. Specifically, these shocks and their frequency significantly influence the choice of cooperative pest and disease control behavior among farmers with junior high school education or above and large-scale farmers, while they have no significant impact on farmers with primary school education or below and small-scale farmers.